An Atlas of Functions with Equator, the Atlas Function Calculator - Oldham, Keith B.; Myland, Jan; Spanier, Jerome (Springer New York : Imprint: Springer, 2009)
This second edition of An Atlas of Functions, with Equator, the Atlas Function Calculator, provides comprehensive information on several hundred functions or function families of interest to scientists, engineers and mathematicians who are concerned with the quantitative aspects of their field. Beginning with simple integer-valued functions, the book progresses to polynomials, exponential, trigonometric, Bessel, and hypergeometric functions, and many more. The 65 chapters are arranged roughly in order of increasing complexity, mathematical sophistication being kept to a minimum while stressing utility throughout. In addition to providing definitions and simple properties for every function, each chapter catalogs more complex interrelationships as well as the derivatives, integrals, Laplace transforms and other characteristics of the function. Numerous color figures in two- or three- dimensions depict their shape and qualitative features and flesh out the reader's familiarity with the functions. In many instances, the chapter concludes with a concise exposition on a topic in applied mathematics associated with the particular function or function family. Features that make the Atlas an invaluable reference tool, yet simple to use, include: full coverage of those functions-elementary and "special"-that meet everyday needs a standardized chapter format, making it easy to locate needed information on such aspects as: nomenclature, general behavior, definitions, intrarelationships, expansions, approximations, limits, and response to operations of the calculus extensive cross-referencing and comprehensive indexing, with useful appendices the inclusion of innovative software--Equator, the Atlas Function Calculator the inclusion of new material dealing with interesting applications of many of the function families, building upon the favorable responses to similar material in the first edition.